Decreased epithelial and plasma miR‐181b‐5p expression associates with airway eosinophilic inflammation in asthma. Issue 10 (6th June 2016) - Huo, X.; Zhang, K.; Yi, L.; Mo, Y.; Liang, Y.; Zhao, J.; Zhang, Z.; Xu, Y.; Zhen, G.
Summary: Background: Airway eosinophilic inflammation is a pivotal feature of asthma. Epithelial cells play critical roles in airway eosinophilia. We hypothesized that epithelial microRNAs (miRNAs) are involved in airway eosinophilia. Objective: This study investigated the associations between epithelial and plasma miR‐181b‐5p and airway eosinophilic inflammation, and the possible mechanism by which miR‐181b‐5p participates in eosinophilic inflammation. Methods: Epithelial miRNAs expression was profiled by miRNA array in eight subjects with asthma and four healthy controls. Epithelial miR‐181b‐5p expression was confirmed by quantitative PCR in the subjects for array experiment and another cohort including 21 subjects with asthma and 10 controls. Plasma miR‐181b‐5p was determined by quantitative PCR in 72 subjects with asthma and 35 controls. Correlation assays between epithelial and plasma miR‐181b‐5p expression and airway eosinophilia were performed. The target of miR‐181b‐5p, SPP1, was predicted by online algorithms and verified in BEAS‐2B cells. The role of miR‐181b‐5p in epithelial proinflammatory cytokine expression was examined in an in vitro system. Results: Epithelial miR‐181b‐5p expression was decreased in subjects with asthma. Epithelial miR‐181b‐5p levels were inversely correlated with sputum and bronchial submucosal eosinophilia. Plasma miR‐181b‐5p was decreased and correlated with epithelial miR‐181b‐5p in subjects with asthma. There was a strong inverse correlation between plasma miR‐181b‐5p and airway eosinophilia in subjects with asthma. Plasma miR‐181b‐5p was increased after inhaled corticosteroids treatment. We verified that SPP1 is a target of miR‐181b‐5p. In human bronchial epithelial cells, miR‐181b‐5p regulated IL‐13‐induced IL‐1β and CCL11 expression by targeting SPP1. Dexamethasone restored IL‐13‐induced miR‐181b‐5p down‐regulation and suppressed IL‐13‐induced SPP1, IL‐1β and CCL11 expression. Conclusions and Clinical Relevance: Epithelial and plasma miR‐181b‐5p are potential biomarkers for airway eosinophilia in asthma. MiR‐181b‐5p may participate in eosinophilic airway inflammation by regulating proinflammatory cytokines expression via targeting SPP1.